La Constitución fue norma por ser Pacto Federal - Biglino Campos, Paloma (Teoría y Realidad Constitucional, 2011)
This article is an attempt to analyze the influence exerted by Federalism on the emergence of the normative idea of a Constitution. To this end, it begins by analyzing the curious way in which the Convention of Philadelphia introduced the reference to the Constitution in art.VI.2 of the fundamental charter of the United States, a precept that was born to ensure the new agreement on unity among states versus their tendency to pursue individual interests. Things were no different in Europe. In fact, the Constitution stops being a programmatic rule in the first federal states to appear on our continent in the 19th century. In these formations, it was enforceable law, at least with regard to the member states, as it was the part of the parameter used by the courts to measure the conformity of the legislation of member states to federal law. The idea of the Constitution as an applicable rule is perfected, on our continent, in the 1920 Austrian Constitution, when the concept of a constitution as «total order» forced the equivalence between the federation’s laws and those of the member states, equally subject to constitutional oversight. The last pages are devoted to the way in which the federal structure, by determining the concept of constitutions, influences the model for judicial review of legislation. In the United States, the superposition of a federation on top of the member states implied a dual structure in which the main topic of discussion was the jurisdiction of the federal courts to supervise the laws enacted by the States, first of all, and by the federation, secondly. The concentrated judicial review emerges, in Europe, in federal states that are the consequence of decentralization processes and, among other factors, of the mistrust caused by the fact that the judiciary is solely in the hands of the federation. Este artículo pretende subrayar la influencia que el federalismo ejerció en la aparición de la idea normativa de constitución. Por ello, comienza analizando la curiosa manera en que la Convención de Filadelfia introdujo la mención a la constitución en el art. VI.2 de la norma fundamental estadounidense, precepto que nació para asegurar el nuevo pacto de unión frente a las tendencias de los estados a perseguir sus intereses particulares. En Europa, las cosas no fueron muy distintas. En efecto, la constitución deja de ser norma programática en los primeros estados federales aparecidos en nuestro continente en el siglo XIX. En estas formaciones, era derecho aplicable, al menos en relación con los estados miembros, ya que encabezaba el parámetro que los tribunales utilizaban para medir la adecuación de las leyes de los estados miembros al derecho federal. La idea de constitución como norma aplicable se perfecciona, en nuestro continente, en Constitución austríaca de 1920, cuando la idea de constitución como «orden total», fuerza a equiparar las leyes de la federación y las de los estados miembros, sometidas en igual medida al control constitucional. En las últimas páginas se trata de la manera en que la estructura federal, al determinar la concepción de constitución, influye en el modelo de control de las leyes. En Estados Unidos, la superposición de la federación sobre los estados miembros implicó una estructura dual en la que el principal tema de discusión fue la competencia de la jurisdicción federal para controlar las leyes de los estados, primero, y de la federación, después. El control de constitucionalidad concentrado aparece, en Europa, en los estados federales que son consecuencia de procesos de descentralización, como consecuencia, entre otros factores, de la desconfianza que suscita el hecho de que el poder judicial quede en manos sólo de la federación.